The Legal Impact Of The Land Deed Official Whose Position Is Different From The Place Of Domicile As A Notary - Ardila Taha Taha; Umar Ma’ruf; Widhi Handoko (Jurnal Akta, 2020)
The objectives of this study are: 1) To find out and explain the legal impact of the Land Deed Official whose position is different from the place of domicile as a Notary. 2) To find out the actions and steps that can be taken if in practice a Notary / PPAT gets a different position area. The method of approach used in this study is the Normative juridical approach. Retrieval of data with a library approach. The analysis was carried out qualitatively.Based on the results of data analysis, it can be concluded that: 1) Notary who has been appointed in an office whose position is different from his area of office as a PPAT is temporarily dismissed from his position for violating the obligations and prohibition of office. Regulations regarding this matter are expressly regulated in UUJN. The person concerned is no longer entitled to make a deed, meaning that he no longer has the authority to make any deed, so if he turns out to still make a deed, then the deed concerned only has the power of proof as a deed under the hand. Whereas the PPAT who is appointed in a position whose position is different from his position as a Notary, causing the PPAT in question automatically stops automatically as a PPAT and for that reason, no dismissal decision is needed. Regulations regarding this matter are explicitly regulated in Government regulation number 24 of 2016 on Government regulation number 38 of 1998 on PPAT Position Regulations. 2) Notary / PPAT Actions and Steps that deal with the problems mentioned above must immediately submit an application to the relevant agency (DEPKUMHAM/BPN) to be able to adjust the area of office. In the event that the formation for the area concerned is closed, the relevant person must wait until the formation for the area is opened. In order to continue to carry out his position concerned must choose his work area as a Notary or work area as PPAT. Regulations regarding this matter are explicitly regulated in Government regulation number 24 of 2016 on Government regulation number 38 of 1998 on PPAT Position Regulations.Keywords: Legal Impact; Land Deed Official; Position; Notary.